The Structure of the Heart and its Physiology in Regular Athletes - Worazbaeva Naubaxor Mratbaevna; Shernazarov Farrux (Genius Publishing Group, 2022)
This article describes in detail the structure, physiology of the heart, regular exercise.
Keywords: Cardiovascular system; collective action